Giants of the sea - Cleave, Andrew (Creatures of the ocean., 2020)
Presents an illustrated look at giant ocean creatures around the world, describing their physical traits, behaviors, habitat, life cycle, and conservation. Includes dozens of color photographs, further reading, internet resources, and QR codes that link to educational videos.